Excitability changes of cortical neurons during the postnatal period in rats exposed to prenatal hypobaric hypoxia - Maresová, D; Valkounová, I; Jandová, K; Bortelová, J; Trojan, S (Physiological research, 2001)
Pregnant rats were exposed to intermittent hypobaric hypoxia (at a simulated altitude of 7000 m or 5000 m) and the excitability of cortical neurons of their pups was tested. Stimulation of the sensorimotor cortex of rats prenatally exposed to hypoxia shortened the duration of cortical afterdischarges in 12-day-old rats, but did not change the excitability in 25-day-old animals. Shortening of the first afterdischarge in 35-day-old rats but the prolongation of the first afterdischarge in adult rats (as compared to the duration of cortical afterdischarges in rats not exposed to prenatal hypoxia) were registered. The possible mechanisms of different excitability of cortical neurons in rats prenatally exposed to hypobaric hypoxia are discussed.
Keywords: Epilepsy; epilepsie; Pregnancy; zpožděný efekt prenatální expozice; motorické korové centrum; Electrophysiology; Female; novorozená zvířata; krysa rodu Rattus; Hypoxia; elektrofyziologie; zvířata; neurony; somatosenzorické korové centrum; Somatosensory Cortex; hypoxie; atmosférický tlak; Animals, Newborn; ženské pohlaví; Altitude; Motor Cortex; těhotenství; Neurons; Rats; Atmospheric Pressure; Animals; Prenatal Exposure Delayed Effects; nadmořská výška